Long-term Psychological and Physical Outcomes of Women After Postdural Puncture Headache: A Retrospective, Cohort Study. Issue 4 (22nd December 2021) - Orbach-Zinger, S.; Eidelman, L.A.; Livne, M.Y.; Matkovski, O.; Mangoubi, E.; Borovich, A.; Wazwaz, S.A.; Ioscovich, A.; Zekry, Z.H.B.; Ariche, K.; Weiniger, C.F.
Abstract : ( Eur J Anaesthesiol . 2021;38:130–137) Accidental dural puncture (ADP) occurs in 0.4% to 6% of patients who receive neuraxial analgesia, and a significant number of ADP patients develop postdural puncture headache (PDPH). PDPH is associated with impaired maternal-neonatal bonding, longer hospital stay, limited ambulation and maternal morbidity. While previous studies have investigated long-term physical outcomes associated with PDPH, limited data exists on the associations between PDPH and long-term psychological outcomes, like postpartum depression (PPD) and postpartum posttraumatic stress disorder (PTSD). This study compared the frequency of these outcomes in women with PDPH with a control group of women without PDPH.